Pengaruh Penerapan Strategi SQ4R dalam Meningkatkan Kemampuan Membaca Pemahaman Siswa Kelas V - Aura Zanzabila Zahra; Dadan Djuanda; Dety Amelia Karlina (Jurnal Pena Ilmiah, 2022)
This research was conducted on the basis that the ability to read comprehension is an important ability for students to have as a support for understanding a teaching material in any field of study. One of the efforts to improve reading comprehension skills is to use the SQ4R strategy in learning. The purpose of this study was to determine the effect of the SQ4R strategy in improving students reading comprehension skills. The research method used is a quasi-experimental with non-equivalent control group design. Based on the research that has been done, the average score of students before being given treatment (pretest) was 22,53. Meanwhile, the average score after being given treatment (posttest) was 49,9. This shows that the effect of SQ4R strategy can improve students reading comprehension skills.